The Scope and Legal Nature of the Obligation to Hand Over an End-Of-Life Vehicle - Korzeniowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This paper deals with the issue of mandatory assignation of end-of-life vehicles exclusively to entrepreneurs running a car disassembly or collection centre, and is based on the assumption that the waste management is subject to strict administrative and legal rules. That obligation aims principally at protecting the environment and public health, reducing the quantity of car waste, and enabling the reuse, recycling or other form of reclamation of end-of-life vehicles and their parts. Moreover, reducing the quantity of waste intended for disposal contributes directly to the public health protection.